O6D.5 Electronic waste recycling exposure and hormone levels in workers. (April 2019) - Gravel, Sabrina; Bakhiyi, Bouchra; Lavoué, Jérôme; Verner, Marc-André; Zayed, Joseph; Labrèche, France
Abstract : Background and objective: Electronic waste recycling (e-recycling) exposes workers to several contaminants, including flame retardants that are suspected endocrine disruptors. We aimed to explore the association between polybrominated diphenyl ethers (PBDEs) and hormone levels in the serum of Canadian e-recycling workers. Methods: In a cross-sectional study, blood samples were collected from 85 e-recycling workers (six facilities) and from 15 workers in other types of recycling (two facilities), at the end of a work shift. Socio-demographic information was obtained by questionnaire and body mass index (BMI) was calculated from measured height and weight. Serum concentrations of 13 PBDE congeners were measured as well as thyroid hormones (free and total thyroxine [T4], triiodothyronine [T3], thyroid stimulating hormone [TSH]) and testosterone (free and total). Linear regressions were stratified on sex and adjusted for age, BMI, seniority, smoking status, and type of recycling. Ten participants were excluded because of thyroid or testicular problems. Results: Participants were 23 women and 77 men (mean 40 years old, SD=12 years). Average hormone levels were within the laboratory normal range. In e-recycling, geometric mean concentrations of the most detected congeners were 11, 11 and 20 ng/g lipids for BDE47, BDE153 and BDE209, respectively. Only BDE209 concentrations were higher in e-recycling than in the control group. A two-fold increase in serum BDE209 was associated with a significant increase of 2.48 nmol/L in total T4 in men (p=0.011), and with a close to significant increase in the free/total testosterone ratio of 6% in men (p=0.053). BDE47 and BDE153 were not associated with hormone levels. Conclusions: The clinical significance of high exposure to BDE209 in working adults is yet to be established, but endocrine effects were observed in this population. E-recycling workers are highly exposed to PBDEs among other substances, which may make them more vulnerable to hormonal disruption.